Factors associated with declining under-five mortality rates from 2000 to 2013: an ecological analysis of 46 African countries. Issue 1 (8th January 2016) - Kipp, Aaron M; Blevins, Meridith; Haley, Connie A; Mwinga, Kasonde; Habimana, Phanuel; Shepherd, Bryan E; Aliyu, Muktar H; Ketsela, Tigest; Vermund, Sten H
Abstract : Objective: Inadequate overall progress has been made towards the 4th Millennium Development Goal of reducing under-five mortality rates by two-thirds between 1990 and 2015. Progress has been variable across African countries. We examined health, economic and social factors potentially associated with reductions in under-five mortality (U5M) from 2000 to 2013. Setting: Ecological analysis using publicly available data from the 46 nations within the WHO African Region. Outcome measures: We assessed the annual rate of change (ARC) of 70 different factors and their association with the annual rate of reduction (ARR) of U5M rates using robust linear regression models. Results: Most factors improved over the study period for most countries, with the largest increases seen for economic or technological development and external financing factors. The median (IQR) U5M ARR was 3.6% (2.8 to 5.1%). Only 4 of 70 factors demonstrated a strong and significant association with U5M ARRs, adjusting for potential confounders. Higher ARRs were associated with more rapidly increasing coverage of seeking treatment for acute respiratory infection (β=0.22 (ie, a 1% increase in the ARC was associated with a 0.22% increase in ARR); 90% CI 0.09 to 0.35; p=0.01), increasing health expenditure relative to gross domestic product (β=0.26; 95% CI 0.11 to 0.41; p=0.02), increasing fertility rate (β=0.54; 95% CI 0.07 to 1.02; p=0.07) and decreasing maternal mortality ratio (β=−0.47; 95% CI −0.69 to −0.24; p<0.01). The majority of factors showed no association or raised validity concerns due to missing data from a large number of countries. Conclusions: Improvements in sociodemographic, maternal health and governance and financing factors were more likely associated with U5M ARR. These underscore the essential role of contextual factors facilitating child health interventions and services. Surveillance of these factors could help monitor which countries need additional support in reducing U5M.